RNA sequencing identifies transcriptional changes in the rabbit larynx in response to low humidity challenge - Bailey, Taylor W.; dos Santos, Andrea Pires; do Nascimento, Naila Cannes; Xie, Shaojun; Thimmapuram, Jyothi; Sivasankar, M. Preeti; Cox, Abigail (BMC genomics, 2020)
Voice disorders are a worldwide problem impacting human health, particularly for occupational voice users. Avoidance of surface dehydration is commonly prescribed as a protective factor against the development of dysphonia. The available literature inconclusively supports this practice and a biological mechanism for how surface dehydration of the laryngeal tissue affects voice has not been described. In this study, we used an in vivo male New Zealand white rabbit model to elucidate biological changes based on gene expression within the vocal folds from surface dehydration. Surface dehydration was induced by exposure to low humidity air (18.6% + 4.3%) for 8 h. Exposure to moderate humidity (43.0% + 4.3%) served as the control condition. Ilumina-based RNA sequencing was performed and used for transcriptome analysis with validation by RT-qPCR. There were 103 statistically significant differentially expressed genes identified through Cuffdiff with 61 genes meeting significance by both false discovery rate and fold change. Functional annotation enrichment and predicted protein interaction mapping showed enrichment of various loci, including cellular stress and inflammatory response, ciliary function, and keratinocyte development. Eight genes were selected for RT-qPCR validation. Matrix metalloproteinase 12 (MMP12) and macrophage cationic peptide 1 (MCP1) were significantly upregulated and an epithelial chloride channel protein (ECCP) was significantly downregulated after surface dehydration by RNA-Seq and RT-qPCR. Suprabasin (SPBN) and zinc activated cationic channel (ZACN) were marginally, but non-significantly down- and upregulated as evidenced by RT-qPCR, respectively. The data together support the notion that surface dehydration induces physiological changes in the vocal folds and justifies targeted analysis to further explore the underlying biology of compensatory fluid/ion flux and inflammatory mediators in response to airway surface dehydration.